Characterization of the gut microbiota in urinary calculi patients with preoperative urinary tract infection - Hao Chen; Jing Yuan; Hongmin Zhou; Xiangcheng Zhan; Yuchen Gao; Bowen Chen; Nuer Aihemaiti; Xiao Xu; Yunze Dong; Shuai Liu; Yanhua Chen; Ding Liu; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundUrinary tract infection is one of the most common comorbidities of urinary stones. Disorders of gut microbiota can affect various infectious diseases and the formation of the stones. Therefore, alterations in the gut bacteria profile may be a potential risk factor for the development of infections in patients with urinary tract stones.MethodsWe conducted a retrospective study to analyze the association of urinary tract infections with gut microbiota and serum metabolism in patients with stones.ResultsPatients with urolithiasis were predominantly in combination with diabetes mellitus (11.4% vs. 20%) and hypertension (36.4% vs. 50%). There were no statistically significant differences in hematological and urinary parameters. Compared to negative patients, IL-17A was significantly higher in the positive group (25.0 vs 21.1 pg/ml p = 0.038). The majority of pathogens detected in urine cultures were urease-negative bacteria, and urease-positive bacteria accounted for 15% of the total number of patients. We analyzed the community composition of the two groups of patients and found a significant difference in their β-diversity (p = 0.025), suggesting that dysbiosis of the gut bacteria may be associated with the combination of urinary tract infections in urolithiasis. For identification of crucial bacteria, we found changes in the abundance of both Intestinibacter (p = 0.036) and Dialister (p = 0.039), and abundance of Intestinibacter was positively correlated with IFN-α, IL-12P70 (p<0.05), and especially IL-17A (p<0.01), which may result from differences in translational, ribosomal structural and biosynthetic functions in stone patients (p < 0.05).ConclusionUrolithiasis with gut dysbiosis developed a higher incidence of urinary tract infections, which may be associated with the increasing of Intestinibacter and affect the expression of IL-17A by translational, ribosomal structural and biosynthetic function.